2-Hydroxycinnamaldehyde Inhibits SW620 Colon Cancer Cell Growth Through AP-1 Inactivation - Chung Woo Lee; Seung Ho Lee; Jae Woong Lee; Jung Ok Ban; So Yong Lee; Han Soo Yoo; Jae Kyung Jung; Dong Cheul Moon; Ki Wan Oh; Jin Tae Hong (Elsevier, 2007)
Cinnamaldehyde derivatives isolated from Cinnamomum cassia have been widely used for treating dyspepsia, gastritis, and inflammatory disease as well as cancer. To investigate the anti-tumor activities of several cinnamaldehyde derivatives, we compared the inhibitory effect of cinnamaldehyde derivatives on cell growth and AP-1 transcriptional activity in SW620 human colon cancer cells since AP-1 is a transcriptional factor implicated to control cancer cell growth. Among the derivatives, 2'-hydroxycinnamaldehyde (HCA) most significantly inhibited cancer cell growth and AP-1 transcriptional activity in a dose-dependent manner with an IC50 value of 12.5 and 9 µg/ml, respectively. In further studies on the mechanism, we found that consistent with the inhibitory effect on cell growth, HCA dose-dependently (0 - 20 µg/ml) inhibited DNA binding activity of AP-1 accompanied with down regulation of c-Jun and c-Fos expressions. HCA also induced apoptotic cell death as well as expression of the apoptosis-regulating gene caspase-3, but inhibited the anti-apoptosis regulating gene bcl-2 in a dose-dependent manner. These results suggested that HCA has the most potent inhibitory effect against human colon cancer cell growth, and AP-1 may be an important target of HCA. Keywords:: 2'-hydroxycinnamaldehyde (HCA), AP-1, colon cancer, cell growth inhibition